Assessing Digital Literacy among the Oraon Tribe of Jharkhand: A Study - Pradeep Kumar Mahto; K.L. Mahawar (Recent Trends in Social Studies, 2026)
Digital literacy is essential for inclusion and socioeconomic empowerment in the digital era. This study examines the digital literacy levels of the Oraon tribe in Jharkhand, with a focus on identifying skill gaps, demographic disparities, and barriers to digital access. A mixed-methods approach was employed to gather data from respondents in the Ranchi district, utilizing structured questionnaires and interviews. Male respondents made up the majority (61.5%), with the largest age group being 26–35 years (45.9%), and the majority (34.9%) holding a degree of less than matriculation. Even though many people owned a smartphone, males were much more proficient with technology than females when it came to sending messages (t = 3.096, p <.001), using mobile apps (t = 3.584, p <.001), accessing e-governance services (t = 2.516, p =.013), and finding information online (t = 4.295, p <.001). However, there were no discernible differences in the use of digital payments by gender. The main challenges identified were low educational attainment, limited connectivity, and language limitations. To boost digital inclusion among the Oraon tribe, this study suggests infrastructure upgrades, gender-sensitive training, and locally relevant digital content.
Keywords: ICT access; Oraon tribe; Ranchi; Tribal development; digital literacy